A Study Of Organization Performance For Experimental Structures Of Two, Three and Four Levels - Jones, Halsey R. (Academy of Management Journal, 1969)
The purpose of this research was to investigate the effects of organization levels upon organization performance. The methodology involved the establishment of experimental organizations of four, three, and two levels, and these were evaluated in terms of profitability, communication speed and accuracy, and individual member attitudes. The results of the experiment provide support for the hypothesis that the number of levels in an organization will affect organization performance. It provided limited support for the hypothesis that the fewer the number of levels the better the performance.